Pemberian Kotoran Jangkrik dan Zat Pengatur Tumbuh Dapat Meningkatkan Pertumbuhan dan Produksi Tanaman Bawang Merah (Allium ascalonicum L. ) - Rival Firnanda; Khairil Anwar Tanjung; Farida Hariani; Aisyah Lubis (Program Studi Agroteknologi, Fakultas Pertanian, Universitas Al Azhar Medan, 2024)
Shallot (Allium ascalonicum L.) is a type of plant that is used as a cooking spice in Southeast Asia and other parts of the world. This study aims to determine the effect of cricket droppings and growth regulators and the interaction of cricket droppings and growth regulators on the growth and production of shallots (Allium ascalonicum L.). This research was conducted from March to May 2023. This study used a Factorial Randomized Block Design with 2 factors studied and 3 repetitions where the first factor was cricket droppings (J) which consisted of 4 levels, namely J0 = without cricket droppings, J1 = 1.2 kg per plot, J2 = 2.4 kg per plot, J3 = 3.6 kg per plot. The second factor was growth regulators (Z) which consisted of 3 levels, namely Z0 = without growth regulators, Z1 = 2 ml liter-1 of water per plot, Z2 = 4 ml liter-1 of water per plot. The results showed that the application of cricket droppings had a very significant effect on all observed parameters such as plant height, number of leaves per clump, number of tillers per clump, number of tubers per clump and fresh weight of tubers per clump. The application of growth regulators did not significantly affect all observed parameters such as plant height, number of leaves per hill, number of tillers per hill, number of tubers per hill and fresh tuber weight per hill. Meanwhile, the interaction between cricket droppings and growth regulators did not significantly affect all observed parameters.